2013
DOI: 10.1007/s10482-013-9910-8
|View full text |Cite
|
Sign up to set email alerts
|

High activity catechol 1,2-dioxygenase from Stenotrophomonas maltophilia strain KB2 as a useful tool in cis,cis-muconic acid production

Abstract: This is the first report of a catechol 1,2-dioxygenase from Stenotrophomonas maltophilia strain KB2 with high activity against catechol and its methyl derivatives. This enzyme was maximally active at pH 8.0 and 40 °C and the half-life of the enzyme at this temperature was 3 h. Kinetic studies showed that the value of Km and Vmax was 12.8 μM and 1,218.8 U/mg of protein, respectively. During our studies on kinetic properties of the catechol 1,2-dioxygenase we observed substrate inhibition at >80 μM. The nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 38 publications
1
38
3
Order By: Relevance
“…The presence of a methylsubstituent in ortho ‐position to the hydroxyl group on the aromatic ring led to a significant decrease of the enzyme affinity for the corresponding phenol . CatPL12 did not reveal dependence of activity changes on position and kind of substituents as C12O from Stenotrophomonas maltophilia strain KB2 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The presence of a methylsubstituent in ortho ‐position to the hydroxyl group on the aromatic ring led to a significant decrease of the enzyme affinity for the corresponding phenol . CatPL12 did not reveal dependence of activity changes on position and kind of substituents as C12O from Stenotrophomonas maltophilia strain KB2 .…”
Section: Discussionmentioning
confidence: 88%
“…C12O activity was assayed spectrophotometrically by creating an assay mixture containing 50 µl of three times diluted C12O solution and 0.5 mM catechol as substrate. The final volume was adjusted to 3 ml with 50 mM Tris‐HCl buffer (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our findings the SDS PAGE releaved a band at 35 kDa. Similarly the subunit molecular weight of C12D was estimated to be 31,558 and 34,500 Da from Rhodochrous NCIMB 13259 39 and Stenotrophomonas maltophilia strain KB2 40 , receptively. Three bands were observed in Zymography which were in agreement with the findings of three isoenzymes of C12D that have been reported from Pseudomonas arvilla C-1, which were formed by the combination of two nonidentical subunits 41 .…”
Section: Resultsmentioning
confidence: 99%
“…S. maltophilia strains are also able to promote growth of its plant host and to inhibit growth of phytopathogens through the production of chitinases, proteases, lysozyme, and secondary metabolites such as pyrrolnitrin, enterobactin and phenazine [Wu et al 2015;Zhang and Yuen 1999]. It has been reported that S. maltophilia strains are capable of degrading xenobiotics such as monocyclic aromatic hydrocarbons [Guzik et al 2013], drugs [Guzik et al 2009], and pesticides . Additionally, in many of S. maltophilia strains resistance to heavy metals was also observed [Ghosh and Das 2013] To effectively promote growth of its plant host, bacterium must possess certain traits that make it possible to penetrate plant avoiding response from the immune system and to establish colony in the internal tissues of plant.…”
Section: Introductionmentioning
confidence: 99%